Maternal separation produces alterations of forebrain brain-derived neurotrophic factor expression in differently aged rats - Wang, Qiong; Shao, Feng; Wang, Weiwen (Frontiers in Molecular Neuroscience, 2015)
Early postnatal maternal separation (MS) can play an important role in the development of psychopathologies during ontogeny. In the present study, we investigated the effects of repeated MS (4 h per day from postnatal day [PND] 1–21) on the brain-derived neurotrophic factor (BDNF) expression in the medial prefrontal cortex (mPFC), the nucleus accumbens (NAc) and the hippocampus of male and female juvenile (PND 21), adolescent (PND 35) and young adult (PND 56) Wistar rats. The results indicated that MS increased BDNF in the CA1 and the dentate gyrus (DG) of adolescent rats as well as in the DG of young adult rats. However, the expression of BDNF in the mPFC in the young adult rats was decreased by MS. Additionally, in the hippocampus, there was decreased BDNF expression with age in both the MS and socially reared rats. However, in the mPFC, the BDNF expression was increased with age in the socially reared rats; nevertheless, the BDNF expression was significantly decreased in the MS young adult rats. In the NAc, the BDNF expression was increased with age in the male NMS rats, and the young adult female MS rats had less BDNF expression than the adolescent female MS rats. The